(untitled) (Modern education and development, 2025)
This article explores the phenomenon of first language (L1) interference in learning English, specifically focusing on Uzbek speakers. L1 interference occurs when a learner’s native language’s grammatical rules, phonology, lexicon, and cultural norms negatively impact the process of acquiring a new language. This article aims to identify the most common areas of L1 interference for Uzbek speakers learning English and to propose pedagogical strategies to mitigate these challenges. The article draws upon a review of existing literature on L1 interference and analyzes case studies of Uzbek-speaking learners of English to identify key areas of difficulty. It demonstrates that L1 interference is a common difficulty in learning English and requires attention from both teachers and learners. The article also provides practical recommendations to minimize L1 interference and improve the efficiency of language learning.